(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article examines the features of the use of the lexemes "white” and " black" in the modern Kazakh language in the literal and figurative meanings. The use of the typical colors " white " and " black" in the meanings of adjectives, nouns, as well as figurative meanings and as part of phraseological units is analyzed, examples from dictionaries are carried out. In the article, the colors "white" and "black" are studied not only in the linguistic aspect, but also in the ethnolinguistic and linguoculturological aspects.